Introduction: Building decolonial learning and teaching through connecting to our diverse pasts: a case for ukuzilanda - Tyler, Robyn (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
The authors of this special issue – Nondwe Mpuma, Martina van Heerden, Khanyiso Jonas and Robyn Tyler - are part of a cohort of early career academics in the Arts and Humanities Faculty at the University of the Western Cape. We are joined by co-author Athambile Masola from the University of Cape Town. We are all fewer than 5 years into our permanent position as a lecturer at our institution. We come from Lubaleko, Kariega, Durban, eMonti and Cape Town and we speak isiXhosa, Afrikaans, English and isiZulu. Our academic disciplines within Arts and Humanities include Linguistics, English Literature, Sociology, Academic Literacies and Historical Studies. The foregrounding of our academic, geographic and linguistic identity positions within the body of this introduction is intentional.